An agricultural sector assessment of biological asset valuation challenges with inputs considered from valuers - van Biljon, Marilene; Wingard, Christa (International Journal of Financial, Accounting, and Management, 2020)
Purpose: Establish whether the industry biological asset fair valuing challenges are country-specific or agricultural-sector specific. Determine how the inputs and challenges experienced by the valuers relate to the industry challenges. Research Methodology: Descriptive, qualitative conceptual content analysis of financial reports of 50 listed organizations across 10 countries from 2012 to 2015; with relational content analysis through in-person interviews with 24 biological asset valuers. Results: This paper contradicts prior research as no correlation was identified between large agricultural organizations and the extent of biological asset disclosures. The biological asset valuation and disclosure challenges are not country-specific or agricultural-sector-specific and the inconsistency in factors applied by the valuers appears to impact the industry challenges directly. Limitations: As biological assets are only held by agricultural organizations of which not all fair value the assets to report thereon – limiting the number of interviews to 24. Data collected via the interviews represent the challenges and valuation considerations of the individuals and their exposure to biological asset valuations. Contribution: This research analyzed and categorised the biological asset valuation challenges to determine whether it is country-specific and/or unique to an agricultural sector. The input factors and challenges experienced by the valuers in relation to the reporting challenges allow a relational analysis of the industry challenges. Keywords: Biological asset valuation, Decision-enhancing disclosures, Fair value accounting, Users of financial statements, Valuation elements